Analisis Efektivitas Pembelajaran Berbasis Daring Selama Covid-19 Pada Peserta Didik Kelas MIPA SMA Negeri 1 Sakra - Maizani, Nur; Sofia, Baiq Fara Dwirani; Muti’ah, Muti’ah; Siahaan, Jeckson (Chemistry Education Practice, 2024)
This study aims to find out the effectiveness of online based learning during covid 19 for students of class XI dan XII MIPA SMA Negeri 1Sakra. This type of research is a qualitative descriptive research. Research population as many as 189 students with a sample of 127 students. Technique of  sampling using simple random sampling. Data collection using a closed questionnaire with likert scale that has been tested validity and reliability. Techniques of analysis data using descriptive statistical analysis techniques. The 4 effectiveness indicators measured in this study are activity or student involvement an average value of 2,58, barriers or obstacles that occur in the learning process an average value of 1,94, the quality of the media used an average value of 2,39 and the understanding of students in online chemistry an average value of 1,96. The results of the study indicate that the effectiveness of online learning in students of SMA Negri 1 Sakra with 4 indicators that fall into the low category with an average value of 2,42 which lies in the interval 1,53≤ x ≤ 2,5.